"Our Job is that Whole Gray Zone in Between There": Investigating Genetic Counselors' Strategies for Managing and Communicating Uncertainty. Issue 13 (9th November 2020) - Zhong, Lingzi; Woo, Jihun; Steinhardt, Mary A.; Vangelisti, Anita L.
ABSTRACT: Ample research suggests that uncertainty is a major concern for individuals undergoing genetic testing and for genetic mutation carriers, and that their management of uncertainty is largely influenced by healthcare providers, including genetic counselors (GCs). Indeed, uncertainty is inherent in genetic testing results. To help patients grapple with uncertainty, GCs need to effectively manage the uncertainty inherent in genetic testing and communicate it appropriately to patients. The present study aimed to identify GCs' strategies for managing uncertainty and communicating uncertainty to patients. Eighteen GCs participated in five focus group interviews, and the data were analyzed using a grounded theory approach. Findings indicated that GCs used three main strategies to manage uncertainty: becoming lifelong learners, normalizing uncertainty, and seeking social support. To communicate uncertainty to patients, GCs also used three different strategies: engaging in open and honest communication, adapting to patients' needs, and focusing on known information. The implications of these findings for uncertainty theories and for conceptual frameworks of GCs' clinical communication are discussed.